Evaluation Of Evacuation Routes And Fire Prevention Management On High Rise Buildings (Case Study: Millenium ICT Center, Medan) - Novrial; Ginting, G. N (Jurnal Koridor, 2019)
In the form of evacuation routes, safety handling must be prioritized especially in high-rise buildings. When the fire occurs, the most important thing apart from extinguishing the fire is to bring the occupants out of the building as soon as possible to prevent any casualties. It is necessary to take effective, efficient and integrated fire hazard prevention measures in a management system so that its implementation and renewal can follow the needs. This is also regulated in building regulations and is technically regulated in the Indonesian National Standard. Shopping center building is for example. Shopping center should put more attention to the accessibility aspects of evacuation routes for users. The scoping study of Millennium ICT Center includes the existence of facilities and infrastructure for evacuation and fire management of buildings, evacuation time of building residents, using descriptive study methods with quantitative analytical, and simulation methods using Rockwell Arena Simulation Software. The purpose of this study is to evaluate the effectiveness of accessibility to facilities, infrastructure, and building fire management of Millennium ICT Center as well as evacuation route travel time meet the requirements, safety and comfort standards of building users.